How the Prevalence of Pulp Stone in a Population Predicts the Risk for Kidney Stone - Movahhedian, Najmeh; Haghnegahdar, Abdolaziz; Owji, Fatemeh (Iranian Endodontic Journal, 2018)
Introduction: Conflicting researches exist on relationship between pulp stones and systemic disorders. Nephrolithiasis is a common disease with severe pain and discomfort with increasing prevalence worldwide. The purpose of this study is to evaluate the correlation between pulp and kidney stones to help find a method for early detection of kidney stones. Methods and Materials: the sample of this case-control study comprised of 154 subjects (77 patients with and 77 patients without kidney stone approved by sonographic examination). Two oral and maxillofacial radiologists evaluated their panoramic images for the presence of pulpal stones. Results: A total of 42.9% of subjects showed pulp stones. Most of the teeth with pulp stone in case and control groups were molars (86.30% and 72.97%, respectively). In the group with kidney stones, pulp stones were detected in 38 patients (49.4%), while in the control group, they were detected in 28 subjects (36.4%). Although there was not a significant relationship between the presence/absence of pulp stone and kidney stone (P=0.143), there was statistically significant association between number of teeth with pulp stone in a patient and the presence of kidney stone (P<0.013). The chance of having kidney stone is 5.78 times higher in the subjects having pulp stone in three teeth or more (≥ 3 teeth). Conclusion: Although there is not a correlation between the presence of pulp and kidney stone, the chance of having kidney stone is 5.78 times higher in the subjects with ≥ 3 teeth having pulp stone. Thus, the number of teeth with pulp stone can serve as a predictor for possibility of having kidney stone. Keywords: Dental Pulp Stone; Kidney Stone; Nephrolithiasis; Pulp Calcification; Radiography